Georgia Architectural and Historic Properties Survey of 901 Floyd Street, Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 901 Floyd Street, Valdosta, Ga., December 1980. One story house of rectangular plan. Tin gabled roof, gabled porch with square posts. Shiplap siding. Interior chimney. Exposed rafters. Double hung sash windows with 6/6 lights. Set on brick piers. Fair condition. Date of Construction: App. 1910-1920. Part of an area which possibly developed as housing for millworkers at the Valdosta Mill Company. Not significant in terms of National Register district - too many modern intrusions.
Georgia Architectural and Historic Properties Survey of 901 Floyd Street, Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 82.0 MB (86,031,633 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)